1993
DOI: 10.1093/infdis/167.5.1184
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Use of Ganciclovir and Foscarnet to Treat Cytomegalovirus Infection in AIDS Patients

Abstract: Ten patients with AIDS and progressive cytomegalovirus disease were treated with ganciclovir and foscarnet concurrently. The patients had received ganciclovir and foscarnet monotherapy a median of 330 days before receiving combination therapy for a median of 80 days. Nine of the 10 patients responded to the combination. No electrolyte abnormalities were noted during combination therapy, but rates of neutropenia (relative rate, combination vs. ganciclovir, 1.99; P = .229) and thrombocytopenia (relative rate, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…A small study of patients that received solid organ transplantation 25 concluded that combined antiviral therapy with ganciclovir and foscarnet are safe and could possibly benefit those patients harboring ganciclovir-resistant strains. Moreover, combined use of ganciclovir and foscarnet could be more aggressive therapeutic approach due to their presumed synergy 9 . Considering these aspects, some authors suggest the use of combined therapies for central nervous system CMV involvement 8,20 .…”
Section: Discussionmentioning
confidence: 99%
“…A small study of patients that received solid organ transplantation 25 concluded that combined antiviral therapy with ganciclovir and foscarnet are safe and could possibly benefit those patients harboring ganciclovir-resistant strains. Moreover, combined use of ganciclovir and foscarnet could be more aggressive therapeutic approach due to their presumed synergy 9 . Considering these aspects, some authors suggest the use of combined therapies for central nervous system CMV involvement 8,20 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible therapeutic approach in these patients could be to combine ganciclovir and foscarnet. These agents show synergy in vitro (41) and, used together, gave good results in both CMV-related neurological and extraneurological infection (29,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Single case reports have described clinical efficacy of the combination of ganciclovir plus foscarnet for treating CMV viremia and/or disease in patients who were suspected to have GCV susceptible virus (Dieterich et al, 1993). Bacigalupo et al (1996) used preemptive GCV plus foscarnet to treat 32 allogenic hemopoietic stem cell transplant (HSCT) recipients who developed CMV antigenemia (>4 cells/200,000).…”
Section: Therapy Of CMV Viremic Diseasementioning
confidence: 99%